2019
DOI: 10.1186/s12935-019-0958-z
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 promotes breast cancer by upregulating PTP1B expression via inhibiting miR-206

Abstract: BackgroundThe long non-coding RNA (lncRNA) urothelial carcinoma-associated 1 (UCA1) is involved in various cancers and often functions through microRNAs. The pro-survival protein PTP1B is known to play important roles in cancer development. However, the connection between UCA1 and PTP1B in breast cancer is not well studied.MethodsIn this study, we first evaluated the correlation between UCA1 level and PTP1B expression in breast tissues, which showed the expression of PTP1B were much higher in the breast tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…36 Additionally, UCA1 improved BC progression through enhancing PTP1B by sponging miR-206. 37 These studies suggested the signal network of lncRNA-miRNA-mRNA in cancer regulation. Our data presented that UCA1 regulated the expression of CDK12 via the direct combination with miR-613.…”
Section: Discussionmentioning
confidence: 99%
“…36 Additionally, UCA1 improved BC progression through enhancing PTP1B by sponging miR-206. 37 These studies suggested the signal network of lncRNA-miRNA-mRNA in cancer regulation. Our data presented that UCA1 regulated the expression of CDK12 via the direct combination with miR-613.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Long non-coding RNA ADPGK-AS1 affects cell proliferation and invasion via miR-542-3p in osteosarcoma [37]. Long non-coding RNA UCA1 can up-regulates PTP1B to enhance cell proliferation through sequestering miR-206 in breast cancer [38]. SNHG8 plays oncogenic roles in the malignancy of esophageal squamous cell carcinoma by sponging miR-411, thus increasing KPNA2 expression [39].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA UCA1 enhanced cell proliferation via modulating miR-206/PTP1B axis in breast cancer. 5 LncRNA DSCAM-AS1 was increased and promoted cell migration and invasion of colorectal adenocarcinoma cells via inhibiting miR-216b. 6 LncRNA TMPO-AS1 restrained cell apoptosis of osteosarcoma by increasing WNT7B expression via inhibition of miR-199a-5p.…”
Section: Introductionmentioning
confidence: 99%